(1360) Investment planning a proposed goal programming approach - montasser, saadia H. (The Institute Of National Planning., 2018)
Several approaches to investment evaluation have proposed to consolidate the multiple objectives into a single aggregate criterion for evaluation. They did so by introducing the concept of a numeration. One of the objectives, usually the one considered the most important, is chosen as a numeration.